Ensaio da monocamada de monócitos para o estudo do significado clínico de alo e autoanticorpos antieritrocitários em pacientes atendidos na Fundação Hemominas – Belo Horizonte - Minas Gerais. - Mariana Martins Godin (2023)
Transfusion of red blood cells is a life-sustaining therapy and is essential in the treatment of anemia or blood loss. However, there are risks associated with blood transfusion, such as the occurrence of a hemolytic transfusion reaction caused by antibodies. In the routine of Hemotherapy services, patients relatively frequently appear who have developed anti-erythrocyte allo- or autoantibodies, often making it impossible to find compatible red blood cells for safe transfusion. In this context, Sickle Cell Disease stands out for presenting much higher rates of alloimmunization as a result of exposure to donor red blood cells. Therefore, it is crucial to provide tests that contribute to medical decisions regarding the authorization of transfusions when there are no compatible red blood cells. The Monocyte Monolayer Assay (MMA) has emerged as a promising tool for distinguishing clinically significant anti-erythrocyte allo- and autoantibodies. The objective of this study was to evaluate MMA in the routine of the Central de Imuno-Hematologia of Fundação Hemominas to define the clinical significance of anti-erythrocyte allo and autoantibodies in patients treated there, after assay standardization and validation. Three groups of patients were studied: 1. Female patients, including pregnant women, who developed nonspecific alloantibodies (n=8); 2. Patients who had alloantibodies directed to high population frequency antigens (n=15); 3. Patients who had autoantibodies (n=40). The vast majority of alloantibodies directed to high-frequency antigens in the population, as well as autoantibodies, were not clinically relevant by MMA. This understanding can avoid the need to search for rare blood in the state and even nationally, speeding up hemotherapy care for patients who do not have compatible red blood cells. There was no correlation between the reaction intensity of the cross match test or Direct Antiglobulin Test post antibody adsorption and the positive results for MMA. This reinforces the practice of not releasing “less incompatible” blood to the patient in transfusion practice. Furthermore, the monitoring, by MMA, of a pregnant woman alloimmunized by Anti-M, whose fetus presented Perinatal Hemolytic Disease, paved the way for the importance of this test in the maternal-fetal context. The results from the present study allow us to conclude that it was possible to provide hemotherapy assistance to patients without compatible red blood cells, in addition to pointing out a promising path for applying MMA in obstetric monitoring.